Performance and carcass characteristics of finishing steers fed dried, full-fat corn germ - T.J. Kessen; M.J. Sulpizio; M.F. Spire; R.T. Ethington; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2002)
Three hundred and fifty-eight crossbred beef steers (average initial weight 701 lb) were fed finishing diets containing 0, 5, 10, or 15% full-fat corn germ to evaluate effects on growth performance and carcass characteristics. Steers were placed into dirt-surfaced feedlot pens (12 to 16 head each) in December 2000 with a total of six pens per diet. Average daily gains during the 155-day finishing period were 2.83, 2.99, 3.01 and 2.93 lb/day for cattle fed 0, 5, 10, and 15% corn germ, respectively. Dry matter intakes decreased linearly (P<0.05) with increasing concentrations of full-fat corn germ in the diet. Relative to cattle fed no corn germ, efficiencies were improved by 8, 11, and 9% for cattle fed 5, 10, or 15% germ, respectively. Feeding corn germ also reduced the incidence of liver abscesses (P<0.05) compared to cattle fed the control diet. Dried, full-fat corn germ can be used successfully in cattle finishing diets to increase energy density and animal performance.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Corn germ; Fat supplementation